Functional Modulates Derived From Short Adjectives and Predicates in the Russian Language - Tatyana A. Shigurova, Victor V. Shigurov, (Opción, 2019)
The article presents the results of a comprehensive analysis of the short adjectives and predicates’ functional modalisation, denoting assessment of visual and auditory perception or the level of knowledge about an object. As a result, in the Russian language there is a considerable amount of parenthetical modal words derived from adverbs and adjectives and preserving, with a few exceptions, live semantic correlation to the original lexemes. In conclusion, the linguistic transposition of short adjectives used in predicative and impersonal-predicative positions into the category of parenthetical modal words is a very complicated process.